Tungsten isotopes in bulk meteorites and their inclusions—Implications for processing of presolar components in the solar protoplanetary disk. (3rd August 2015) - Holst, J. C.; Paton, C.; Wielandt, D.; Bizzarro, M.
Abstract We present high precision, low‐ and high‐resolution tungsten isotope measurements of iron meteorites Cape York (IIIAB), Rhine Villa (IIIE), Bendego (IC), and the IVB iron meteorites Tlacotepec, Skookum, and Weaver Mountains, as well as CI chondrite Ivuna, a CV3 chondrite refractory inclusion (CAI BE), and terrestrial standards. Our high precision tungsten isotope data show that the distribution of the rare p‐process nuclide 180W is homogeneous among chondrites, iron meteorites, and the refractory inclusion. One exception to this pattern is the IVB iron meteorite group, which displays variable excesses relative to the terrestrial standard, possibly related to decay of rare 184Os. Such anomalies are not the result of analytical artifacts and cannot be caused by sampling of a protoplanetary disk characterized by p‐process isotope heterogeneity. In contrast, we find that 183W is variable due to a nucleosynthetic s‐process deficit/r‐process excess among chondrites and iron meteorites. This variability supports the widespread nucleosynthetic s/r‐process heterogeneity in the protoplanetary disk inferred from other isotope systems and we show that W and Ni isotope variability is correlated. Correlated isotope heterogeneity for elements of distinct nucleosynthetic origin (183W and 58Ni) is best explained by thermal processing in the protoplanetary disk during which thermally labile carrier phases are unmixed by vaporization thereby imparting isotope anomalies on the residual processed reservoir.